Morphological identification and molecular characterization of Podosphaera xanthii causing powdery mildew disease on zigzag plant (Pedilanthus tithymaloides) - Roslen @ Rosdin, Aziera (2017)
Pedilanthus tithymaloides (Euphorbiaceae; known as `Zigzag plant`, ‘Jacob's ladder,’ ‘Devil's Backbone’) is a shrub perennial and succulent spurge. Powdery mildew is a common disease on ornamental plants and vegetables production such as cucurbits plants. These fungi have been reported to cause losses due to its important pathogen. It can reduce an ornamental value if Zigzag plant is grown in a garden or nursery. The identification of obligate parasite has not always been made accurately. Recently, taxonomic concepts for powdery mildew fungi use molecular DNA analyses for accurate identification at the species level. The fungus from symptomatic tissues was identified as Podosphaera xanthii based on morphological characteristics and rDNA Internal Transcribed Sequence (ITS) analysis. Leaves of Zigzag plant were covered with white fungal mycelia, abundant powdery mildew conidia, with the ultimate development of necrosis on symptomatic tissues. Conidia were hyaline, ellipsoid, produced in long chains (seven to eleven conidia per chain), and approximately 32.5 μm long and 20.1 μm wide. Conidiophores were erect, with a foot cell straight or slightly flexuous, approximately 240 μm in long. It had fibrosin body structures. However, chasmothecia were not observed on a surface of the infected leaves. Conidial DNA was subjected to polymerase chain reaction (PCR) using universal primers designed to amplify internal transcribed spacer (ITS) region of Podosphaera xanthii. ITS5-Forward and ITS4-Reverse were universal primers used in this study. The size of amplicons was approximately 580 bp. The ITS sequence of powdery mildew was sequenced and ITS sequence data indicated 100% homology to the ITS sequences of Podosphaera xanthii infecting Cynanchum auriculatum (KU711923) and Kalanchoe blossfeldiana (KR049082). On the basis of morphological characteristics and ITS sequence analysis, pathogen infecting the leaves of Pedilanthus tithymaloides was identified as Podosphaera xanthii.